INTEGRATING GREEN HUMAN RESOURCE MANAGEMENT AND GREEN INNOVATION TO ENHANCE ENVIRONMENTAL SUSTAINABILITY AND EMPLOYEE PERFORMANCE THROUGH SUSTAINABLE COMPETITIVE ADVANTAGE - Bambang Raditya Purnomo; Sukesi, Sukesi (SULTANIST: Jurnal Manajemen dan Keuangan, 2026)
This study investigates the role of Green Human Resource Management (GHRM) and Green Innovation in improving employee performance and environmental sustainability through Sustainable Competitive Advantage (SCA) as an intervening variable. The study aims to bridge the gap between human resource management and environmental science by demonstrating how green-oriented HR practices and innovation contribute not only to organizational performance but also to ecological outcomes such as energy efficiency, waste reduction, and greenhouse gas (GHG) emission mitigation. Data were collected from 87 employees of PT Segar Murni Utama, a company implementing environmentally responsible operational practices. Partial Least Square–Structural Equation Modeling (PLS-SEM) was used to test the hypotheses. Results indicate that both GHRM and Green Innovation have significant direct effects on SCA and employee performance. Moreover, SCA mediates the relationship between GHRM, Green Innovation, and employee performance. These findings suggest that adopting GHRM and Green Innovation policies enhances not only human capital effectiveness but also the company’s contribution to Sustainable Development Goals (SDG 12 – Responsible Consumption and Production, and SDG 13 – Climate Action). The study highlights the strategic importance of aligning HR and innovation policies with environmental sustainability objectives to foster long-term competitive advantage and ecological resilience.